Violation of Maxims of Quality and Quantity in Anime Spy X Family Episode 1-3: Pragmatic Study - Raditya Jagadhita; Elisa Debora Silalahi; Yufita Ria Oktiani (Journal of Japanese Language Education and Linguistics, 2024)
The anime genre has gained significant popularity as a source of entertainment, and Spy X Family stands out as a prominent example of this phenomenon. The objective of this study is to examine the violations of the principles of quality and quantity in the Spy X Family. The study is characterized by its descriptive nature and utilizes a qualitative methodology. Observational data was collected by listening and taking notes, and subsequently examined utilizing translational matching methods. A total of four cases of violation of the maxim of quality and four instances of violation of the maxim of quantity were identified in the findings. These infractions are ascribed to the characters' origins as spies, which require them to furnish information that does not accurately represent the real situation.